Shell Beach [large type] - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay, 2023)
"A man adrift . . . Noah Hearst is leaving a life he's spent twelve years building. Professionally, a losing battle for his job after a hostile takeover. Personally, signing away his marriage in a split that was a long time coming. Now, the difficult part: deciding who he is, what he wants, and where to go next. Maybe it's time to realize a dream that's carried him through hard times: owning a boat. Traveling the ocean, exploring new ports, embracing the endless horizon. Blissful. Impractical. Impossible? For now, the dream alone gives Noah the strength to move forward . . . An unexpected lifeline . . . Jenna Greaves is an end-of-life nurse, devoted till her charges' final breath. She's been called a confidante, a surrogate daughter, and a best friend. She is all those to Dino Vicenza, a secretive millionaire who refuses to even speak with his greedy and impatient family. Gradually, Jenna and Dino bond over something rather unusual; she shares the old man's passion for sailing the open seas. With his passing comes an unexpected bequest: a luxury yacht that invites Jenna to break free of old chains, if only she might find someone to help steer her toward new horizons. One twist of fate and Noah and Jenna are brought together in the most unexpected way to navigate their future - and discover more about life, each other, and themselves than they ever imagined."--